1997
DOI: 10.1002/(sici)1096-8628(19971219)73:3<314::aid-ajmg16>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Educational material about genetic tests: Does it provide key information for patients and practitioners?

Abstract: Genetic testing for common conditions will be used increasingly in primary care, but resources for patient counseling are decreasing. It is also necessary that primary care practitioners be better equipped to do basic genetic counseling. Therefore, the quality of informational materials for practitioners and patients is important. It was unknown how often key elements recommended by policy groups were actually included in such material. It was our aim to determine the content of printed informational material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…3 To present "balanced" information, it has been suggested that a relatively equal percentage of the negative as well as the positive aspects of testing should be highlighted, alongside the neutral ones. 39 Cho et al 54 described 10 critical elements that are needed to evaluate the content of informational materials, and these might well be used in the development of educational material about CF carrier screening. By whom and how the information should be provided is a matter that needs further serious consideration, as has also been suggested by Mennuti et al 55 Understanding the consequences of the test results was discussed in most pilot studies.…”
Section: Participation Is Voluntarymentioning
confidence: 99%
“…3 To present "balanced" information, it has been suggested that a relatively equal percentage of the negative as well as the positive aspects of testing should be highlighted, alongside the neutral ones. 39 Cho et al 54 described 10 critical elements that are needed to evaluate the content of informational materials, and these might well be used in the development of educational material about CF carrier screening. By whom and how the information should be provided is a matter that needs further serious consideration, as has also been suggested by Mennuti et al 55 Understanding the consequences of the test results was discussed in most pilot studies.…”
Section: Participation Is Voluntarymentioning
confidence: 99%
“…A leaflet with key information, which can be read at home, significantly improves understanding and recall of information. 39,40 Moreover, presentation of risk information influences information processing and subsequent decision making. 41,42 Risk can be presented in distinctive ways: as a percentage or a proportion, in a numerical or verbal manner, as a single figure or as a relative risk, stressing the positive or negative consequences.…”
Section: Decision Counsellingmentioning
confidence: 99%
“…The Task Force indicated that a protocol for genetic test development would be limited in the absence of appropriate data pertaining to analytic and clinical validity, significance, and usefulness of predictive tests and measures of laboratory quality and reimbursement of laboratory test costs by the various health insurance providers (14 -16). The increasing number of genetic tests, whether provided by nonprofit organizations, requiring only Institutional Review Board approval and/or Clinical Laboratory Improvement Act certification (not regulated by FDA) or by biotechnology companies as diagnostic kits (regulated by FDA), has gradually elevated the awareness and concerns regarding the information provided to practitioners or patients by biotechnology companies and nonprofit organizations (17,18). A survey reviewing 115 drug labels (17,18) has shown that only 3 of 10 concerns were noted in the majority of these labels (which candidates are appropriate for testing, which clinical conditions require testing, and whether genetic counseling was needed).…”
Section: Pharmacogenetic Determinants Of Response: Regulatory Concernsmentioning
confidence: 99%
“…were referred to in <30% of drug labels. Test performance (sensitivity, specificity, and predictive value) described in f50% of drug labels has been vaguely referred to as accuracy (17,18) without definite measures of performance variables. Nonprofit organizations were more likely to state patient rights and need for counseling in their drug labels, whereas biotechnology companies were more likely to specify the purpose of the test (14,17).…”
Section: Pharmacogenetic Determinants Of Response: Regulatory Concernsmentioning
confidence: 99%